Pattern search method for accelerating Stope boundary optimization problem in underground mining operations. Issue 5 (4th May 2022) - Nikbin, Vahid; Mardaneh, Elham; Asad, Mohammad Waqar Ali; Topal, Erkan
Abstract : The Stope Boundary Optimization (SBO) problem refers to the layout design of production areas (stopes) in an underground mining operation. It falls within the domain of strategic mine planning and a model that addresses this problem aims to maximize profitability, offers optimal management of mineral resources and facilitates decision making around capital investments. The SBO problem is computationally complex and a method that offers solution within a reasonable computation time does not exist. In this article, a combination of a new greedy algorithm and a pattern search technique with an integer programming model is proposed. An implementation of the proposed method on three realistic case studies confirms its efficiency in generating robust solutions with a better optimality gap and considerably less computational effort.